Experimental study on the effects of turbulence intensity on the aeroelastic stability of wind turbine airfoils - Jia, Yaya; Lu, Jiahao; Zhao, Zonghan; Liu, Qingkuan; Lv, Shanning (Experimental thermal and fluid science, 2025)
•Different turbulence intensities oppositely affect airfoil aeroelastic response.•Divide environments with different turbulence intensities into three zones.•In the promoting zone, leading-edge vortices cause airfoil stall flutter.•In the transition zone, four types of aeroelastic responses are observed.•In the suppressing zone, high turbulence reduces boundary layer separation. The trend toward larger wind turbines also makes the aeroelastic stability of ultra-long flexible blades more sensitive to environmental excitations such as turbulence intensity. Using a specialized airfoil designed for large wind turbines as the research subject, synchronized wind tunnel tests of vibration and pressure were performed to systematically study the effects of turbulence intensity on the aeroelastic stability of the airfoil and to explore its underlying mechanisms. The results showed that different values of incoming turbulence intensity had opposite effects on the aeroelastic response of the airfoil. Accordingly, the environment with different turbulence intensities was divided into zones: turbulence-promoting vibration zone, transition zone, and turbulence-suppressing vibration zone. In the turbulence-promoting vibration zone, the appearance from the leading-edge vortex triggered stall flutter in the airfoil, and the stall flutter was restricted to the specific wind speed scope. As the turbulence intensity increased, the wind speed scope for stall flutter advanced and expanded. In the transition zone, the airfoil’s torsional vibration characteristics became extremely complex, and four types of aeroelastic responses were observed: small amplitude random aeroelastic response, stall flutter, special dual-frequency vibration, and buffeting caused by turbulence excitation. In the turbulence-suppressing vibration zone, high turbulence intensity significantly suppressed the separation of the boundary layer at the airfoil’s suction surface, while only two types of aeroelastic responses were observed, corresponding to the first small amplitude random aeroelastic response and the fourth buffeting caused by turbulence excitation in the transition zone, with the amplitude of buffeting significantly smaller than that in the transition zone.